The relevance of the „Magna Carta of Preaching” by Pope Benedict XV - Turowski, ks. Wojciech (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
The task of the Church is to proclaim Christ. In every era of the history of the Church, the question is asked how to do it today and do it fruitfully? This concern was expressed by Pope Benedict XV when he wrote the encyclical Humani generis redemptionem (1917). Placed in a historical context, the article is a synthesis of the early 20th century pope’s thoughts on preaching and preachers. The article shows the relevance of the church document on preaching. The following demands of Benedict XV are still relevant: bishops’ concern for the quality of preaching in dioceses; good formational, intellectual and homiletical preparation in theological seminaries; preachers’ personal concern for their own sanctification in order to effectively preach the Word of God.